La forma “storta”: Conversazione con Francesco Manetti - Mazzocchi, Federica (Mimesis Journal, 2017)
Francesco Manetti, actor, trainer and director, graduated from the Accademia d’Arte Drammatica “Silvio d’Amico”. Since 1998 he has been teaching movement and stage combat. From the beginning he has shown a strong interest in the international theatrical context. He has often worked abroad in such places as Britain, Germany, the United States, Russia and South America. In 2008 he began collaborating with the director Antonio Latella and has been working with his theatre group “stabile/mobile” since 2013 and has performed in several Latella productions. He and Latella first met thanks to his work as a choreographer, movement and physical trainer. In this guise he has worked with Latella on many productions, such as Hamlet’s portraits (2008), Francamente me ne infischio from Gone with the Wind by Margaret Mitchell (2011 e 2013), Santa Estasi (2016). The conversation, which took place on 19th January 2017 in Turin, explored two themes. The first was about the creative relationship between Manetti and Latella, discussing both Manetti’s role as an actor as well as his work on movement in Latella productions. The second discussed several moments of Manetti’s professional history.